Electron acoustic solitary structures and shocks in dense inner magnetosphere finite temperature plasma. Issue 9 (2nd September 2020) - Goswami, Jyotirmoy; Chandra, Swarniv; Sarkar, Jit; Ghosh, Basudev
Abstract : In this paper, a theoretical investigation of nonlinear electron acoustic waves in plasmas containing degenerate electrons at finite temperature, non-degenerate cold electrons and stationary ions has been carried out. We have considered various effects and by employing the standard reductive perturbation technique (RPT), the KdV-Burger equation describing the shock fronts has been studied. The absence of viscous term results in the transformation of KDV-B to KdV equation. The shock fronts have been studied with variations in different plasma parameters. Analytical derivation and numerical simulations have been carried out. The results are important in explaining many phenomena in the inner magnetosphere.